Hormone receptor and HER2 assessment in breast carcinoma metastatic to bone: A comparison between FNA cell blocks and decalcified core needle biopsies. Issue 2 (28th December 2019) - Zeng, Jennifer; Piscuoglio, Salvatore; Aggarwal, Gitika; Magda, Joanna; Friedlander, Maria A.; Murray, Melissa; Akram, Muzaffar; Reis‐Filho, Jorge S.; Weigelt, Britta; Edelweiss, Marcia
Abstract : Background: Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) immunohistochemistry (IHC) guide the clinical management of breast cancer metastases. Decalcification of bone core needle biopsies (CNBs) can affect IHC. In the current study, the authors sought to define whether fine‐needle aspiration (FNA) would be a better alternative to CNB for reliable IHC. Methods: Patients with breast cancer metastases to bone that were sampled by both CNB and FNA were selected. ER, PR, and HER2 were performed in FNA cell blocks (FNA‐CBs) and concurrent decalcified CNBs. Discrepancies were classified as minor when there was a difference of up to 30% nuclear staining in IHC for ER and PR between paired samples and as major when a clinically relevant change was observed (ie, positive vs negative). Quantitative reverse transcriptase–polymerase chain reaction of ESR1 messenger RNA levels was performed on FNA/CNB pairs with discrepancies for ER IHC. IHC status of the primary breast carcinoma was recorded. Results: Concordance rates for ER, PR, and HER2 were 89%, 67%, and 93%, respectively, between FNA‐CB and CNB pairs from 27 patients. Major discrepancies were noted in approximately 11% of FNA/CNB pairs for ER IHC and in 33% of FNA/CNB pairs for PR. ESR1 messenger RNA levels of FNA/CNB matched samples were similar and did not explain the differences in ER IHC expression in the majority of cases. Two of 27 FNA/CNB pairs had different results for HER2 IHC that changed from negative on CNB to equivocal (2+) on FNA‐CB. Both cases had prior HER2 amplification by fluorescence in situ hybridization. Conclusions: FNA‐CB and CNB appear to constitute acceptable methods for the assessment of ER, PR, and HER2 for clinical decision making. Abstract : Both fine‐needle aspiration (FNA) and core needle biopsy (CNB) constitute acceptable methods for the assessment of estrogen receptor (ER), progesterone receptor, and human epidermal growth factor receptor 2 (HER2) for clinical decision making. In the current study, approximately 50% of all ER‐positive concordant FNA/CNB pairs are found to demonstrate stronger staining and a higher percentage of staining for ER in the FNA cell block samples when compared with the paired CNB.